Post-pandemic consumer behavior towards e-commerce and retail stores in United States - Morales, Milagros (Revista Venezolana de Gerencia, 2021)
COVID-19 profoundly impacted consumer behavior and psychology; this impact is perceived in social habits and shopping changes. Online stores have successfully boosted their sales, to the detriment of retail stores. This article aims to provide statistical analysis and evaluate consumers’ buying behavior by age groups toward retail and online stores for showing recommendations at online store entrepreneurs and retail store owners; thus, optimize costs and have higher sales projections. The methodology used is based on statistical data from various sources and databases such as Statista, United States Census Bureau, and international organizations, contrasted with the information obtained from 314 surveys conducted with consumers in different cities of the United States. In this study, statistical data and surveys upon groups of people were between twenty-two (22) to eighty (80) years old were analyzed. As a result, an increase in online shopping preferences was obtained, where the youngest population group leads the consumption in virtual platforms due to their familiarity with technology. In conclusion, there is a significant increase in online shopping, which is exacerbated by the pandemic.